Biochemical and physiological changes on three commercial marine fish species to extreme weather events - Vieira, Ricardo Jorge Almeida (2017)
The effect of climate change is an issue of major concern to the scientific community and politicians, with the register, at the past decades, of extreme climate events worldwide. A biomarker based biomonitoring program represents a promising approach, due to its usage to assess the health status of organisms with the biochemical response may be used as early-warning signal of chemical (e.g. pollutants) and environmental stress conditions. However, it is of high importance to develop further approaches, to identify standard key species and organs to diagnose and determine damages caused by severe weather events in studies in situ. This work aims to investigate biomarker responses, in situ, in the liver and at the brain of three marine fish species (Dicentrarchus labrax, Platichthys flesus and Solea solea), from the Mondego estuary (Portugal), during two distinct extreme climatic events (drought (2012) and flood (2014)) in order to determine their baseline levels and to identify the organ to be used as endpoint in ecotoxicological studies. In addition, biochemical analyzes were supplemented with physiological indices of the sampled organisms, diagnosing their physiological state and implications for the antioxidant potential. Severe climatic events had distinct modes of action affecting the physiological condition of the studied species. Biochemical experimental approach shows that the brain has a low antioxidant defense system compared to the liver, increased ROS accumulation rates, making it particularly susceptible to oxidative damage during the dry event. In the flood event, the antioxidant potential of the brain compared to the liver revealed higher difficulty in detoxification of xenobiotic compounds. According to higher oxidative sensitivity of the brain, this organ shows to be a good indicator to assess the influence of climate change in aquatic ecosystems, using the liver as a reference organ, less sensitive to the factors above mentioned, although until now the organ often used in the analysis of oxidative metabolism.